2018
DOI: 10.1016/j.resmic.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the lipid composition of Bradyrhizobium cell envelope reveal a rapid response to water deficit involving lysophosphatidylethanolamine synthesis from phosphatidylethanolamine in outer membrane

Abstract: We evaluate the behavior of the membrane of Bradyrhizobium sp. SEMIA6144 during adaptation to polyethylene glycol (PEG). A dehydrating effect on the morphology of the cell surface, as well as a fluidizing effect on the membrane was observed 10 min after PEG shock; however, the bacteria were able to restore optimal membrane fluidity. Shock for 1 h caused an increase of lysophosphatidylethanolamine in the outer membrane at the expense of phosphatidylcholine and phosphatidylethanolamine (PE), through an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Model systems such as MLV are useful to predict how the lipid components of cell membranes will behave (Cesari et al, ). The fluorescent polarization assay using MLV synthesized from lipids of cells exposed to Cr(VI) and Cr(VI) + phenol for 16 h seems to confirm the rigidity effect produced on the membrane mainly by changes in PL, such as the decrease in PtdEtn and the increase in Ptd2Gro.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Model systems such as MLV are useful to predict how the lipid components of cell membranes will behave (Cesari et al, ). The fluorescent polarization assay using MLV synthesized from lipids of cells exposed to Cr(VI) and Cr(VI) + phenol for 16 h seems to confirm the rigidity effect produced on the membrane mainly by changes in PL, such as the decrease in PtdEtn and the increase in Ptd2Gro.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, PLA 2 activity was determined after 1 h of exposure to both contaminants, while PL composition was determined after 16 h, so lysoPtdEtn may not be constant over time, as was also observed by Cesari et al (2018) in Bradyrhizobium SEMIA6144 cells exposed to polyethylene glycol (PEG). Another possibility is that lysoPtdEtn was diluted due to the use of a total membrane fraction to determine the PL profile, because it is well known that this enzyme is the main component in the outer membrane, as was described for Yersinia pseudotuberculosis after shifting the growth temperature from 8 to 37 C or after exposure of the cells to heat shock, and in Bradyrhizobium SEMIA6144 cells after PEG shock (Cesari et al, 2018;Davydova et al, 2016). Moreover, Gcrard (1979) reported that lysoPtdEtn accumulation is often accompanied by an increase in Ptd2Gro, as was found in A. guillouiae SFC 500-1A cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations